On The Origins of Bitcoin:: Stages of Monetary Evolution – Part I - Graf, Konrad S. (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2015)
In this work, the author develops an economic and historical study of the origin of the Bitcoin and of its value as money. In his argument, the author explores the relation between the Bitcoin digital currency and Austrian Economics. Particularly, he discusses Ludwig von Mises’ Regression Theorem and its connection to the evolution of the monetary market, as well as Carl Menger’s seminal evolutionary approach.